Blackout - Black, Peter Jay (Black, Peter Jay. Urban Outlaws., 2015)
"The world's most destructive computer virus has been unleashed, and it's up to the Urban Outlaws--five tough kids dedicated to bringing justice to their city--to destroy it"--